Stabilization of N-, N, N-, N, N′-methylated and unsubstituted simple amidine salts by multifurcated hydrogen bonds. Issue 4 (2006) - Spychała Spychała, Jarosław Jarosław
Abstract : In the light of the usefulness of amidines in medicinal chemistry, this paper considers the effects on biological properties and chemical reactivities of organic molecules affected by intramolecular interactions. The study of chemical shifts has been an important source of information on the electronic structure of amidine salts and their ability to form non-covalent bonds with nucleic acids. The NMR and IR results demonstrate that hydrogen bonds are a force for promoting chemical reactions. The thymine O2 carbonyl oxygen in a close proximity to the amidinium cation does interact with the appropriately spaced amidinium NH donor moieties. The 1 H- 15 N 2D NMR (GHSQC and GHMBC) spectra with natural isotopic abundance of 15 N fully confirm the intramolecular character of the bonds. A rule able to estimate the relative strength of the new multifurcated hydrogen bonds is given. The appearance of the ΔδNH chemical shift differences near zero is due to the strong intramolecular interactions. The strength of the H-bond donation by acetamidines is reflected in the N–H dissociation/recombination process (positive charge shift has been invoked to explain other effects on benzamidines). The temperature dependence of chemical shift for the amidine NH protons in dimethyl sulfoxide solutions is herein discussed.